DUKUNGAN KELUARGA TERHADAP TINGKAT KESEMBUHAN PASIEN COVID-19 DI RUANG ISOLASI RUMAH SAKIT AMINAH 2021 - Agah Nugraha; Rostime Hermayerni Simanullang (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2021)
Corona virus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. Family support is an activity oriented to improve family functions on the basis of raising children and other family activities. in a system and resources that support. This study aims to identify family support for the healing rate of Covid-19 patients in the Isolation Room at Aminah Hospital, Tangerang in 2021. Method: observational analytic used in this research and 23 covid-19 participantn, in this study using the Total Sampling technique. Statistical test used is the Spearman Rank statistical test. Results: The results of study obtained p value = 0.000 <0.05. Conclusion: there is a relationship between family support and the healing of Covid-19 patients. The role of the family is very important. and breaking chain of spread of the Covid-19.